Airborne Transmission of Melioidosis to Humans from Environmental Aerosols Contaminated with B. pseudomallei. - Pei-Shih Chen; Yao-Shen Chen; Hsi-Hsun Lin; Pei-Ju Liu; Wei-Fan Ni; Pei-Tan Hsueh; Shih-Hsiung Liang; Chialin Chen; Ya-Lei Chen (Public Library of Science (PLoS), 2015)
Melioidosis results from an infection with the soil-borne pathogen Burkholderia pseudomallei, and cases of melioidosis usually cluster after rains or a typhoon. In an endemic area of Taiwan, B. pseudomallei is primarily geographically distributed in cropped fields in the northwest of this area, whereas melioidosis cases are distributed in a densely populated district in the southeast. We hypothesized that contaminated cropped fields generated aerosols contaminated with B. pseudomallei, which were carried by a northwesterly wind to the densely populated southeastern district. We collected soil and aerosol samples from a 72 km2 area of land, including the melioidosis-clustered area and its surroundings. Aerosols that contained B. pseudomallei-specific TTSS (type III secretion system) ORF2 DNA were well distributed in the endemic area but were rare in the surrounding areas during the rainy season. The concentration of this specific DNA in aerosols was positively correlated with the incidence of melioidosis and the appearance of a northwesterly wind. Moreover, the isolation rate in the superficial layers of the contaminated cropped field in the northwest was correlated with PCR positivity for aerosols collected from the southeast over a 2-year period. According to pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST) analyses, PFGE Type Ia (ST58) was the predominant pattern linking the molecular association among soil, aerosol and human isolates. Thus, the airborne transmission of melioidosis moves from the contaminated soil to aerosols and/or to humans in this endemic area.